Educational quality, social media and public accountability: A global perspective - Alex Adegboye; Simplice Asongu; Vanessa Tchamyou; Tolulope Temilola Osinubi; Ibukunoluwa Adeyanju (African Governance and Development Institute (AGDI), 2021)
This inquiry relates to the empirical linkages between educational quality, Facebook penetration and accountability dynamics. The empirical investigation is based on the Ordinary Least Squares (OLS) technique and Quantile regression for the conditional linkages which articulate low, middle, and high initial levels of public accountability. It explores a cross-section of 168 countries. The main finding is that there is an overwhelming positive connection between Facebook penetration and accountability dynamics. The established positive nexus is apparent in all quantiles of public accountability. In addition, tertiary and secondary school enrollment positively influence public accountability. By utilizing a novel dataset in analyzing the established nexuses, this study adds to the existing literature on social media and governance (i.e., educational quality, Facebook penetration and accountability dynamics). Similarly, the posture addresses contemporary policy concerns regarding a lack of documentation on the impacts of social media.
Keywords: 330; education; school enrollment; social media; accountability